Factors related to taste sensitivity in elderly: cross‐sectional findings from SONIC study. (12th October 2016) - Uota, M.; Ogawa, T.; Ikebe, K.; Arai, Y.; Kamide, K.; Gondo, Y.; Masui, Y.; Ishizaki, T.; Inomata, C.; Takeshita, H.; Mihara, Y.; Maeda, Y.
Summary: The sense of taste is important, as it allows for assessment of nutritional value, as well as safety and quality of foods, with several factors suggested to be associated with taste sensitivity. However, comprehensive variables regarding taste and related factors have not been utilised in previous studies for assessments of sensitivity. In the present study, we performed cross‐sectional analyses of taste sensitivity and related factors in geriatric individuals who participated in the SONIC Study. We analysed 2 groups divided by age, 69–71 years (young–old, n = 687) and 79–81 years (old–old, n = 621), and performed a general health assessment, an oral examination and determination of taste sensitivity. Contributing variables were selected by univariate analysis and then subjected to multivariate logistic regression analysis. In both groups, females showed significantly better sensitivity for bitter and sour tastes. Additionally, higher cognitive scores for subjects with a fine taste for salty were commonly seen in both groups, while smoking, drinking, hypertension, number of teeth, stimulated salivary flow salt intake and years of education were also shown to be associated with taste sensitivity. We found gender and cognitive status to be major factors affecting taste sensitivity in geriatric individuals.